Narrators Described by Imam Ahmad as “Salih Al Hadith” and Included by Al-Uqayli in Al-Dhuafa al-Kabir: A Critical Study - Qutada Najim Abd Allah, (Islamic Sciences Journal, 2025)
ABSTRACT This study investigates the narrators whom Imam Ahmad Ibn Ḥanbal characterized as “Salih Al Hadith” ,reliable/acceptable in hadith transmission, yet were classified by Al-Uqayli among the weak narrators in his seminal work Al-Dhuafa al-Kabir. The study undertakes a critical evaluation of these narrators by collecting their biographical data, analyzing their transmission reliability, and comparing Imam Ahmad’s assessments with those of other hadith critics in order to ascertain the degree of concordance or divergence between them. The study is structured into an introduction, two main sections, and a conclusion. The first section provides a concise overview of the methodological approaches of Imam Ahmad and Al-Uqayli, while the second section presents a critical analysis of the narrators themselves. The total number of the narrators examined in this study is nine.